Pengelolaan Knwoledge Management Capability Dalam Memediasi Dukungan Information Technology Relatedness Terhadap Kinerja Perusahaan: Pendekatan Reflective Second Order Factor - Meiranto, Wahyu; Puspitasari, Elen; Sari, Irna Maya (AKRUAL: JURNAL AKUNTANSI, 2012)
Abstracthe aim of this research is to observe the influence of information technology complementarities and support of information technology knowledge to corporate performance. Complementarities of information technology are Infrastructure IT, making process IT, Human resources IT and Vendor management IT; and management knowledge are Product, Customer and managerial. The sample’s number of this research are 42 head managers of Main Bank office in Semarang. The research uses questioner method. Data analyzing of this research is full mode Structural Equation Modeling (SEM), evaluated by smartPLS tools by using reflective second order factor approach. The result of this research, aligned with hypothesis that complementarities of four information technology Relatedness Factors, give positive influence to inter unit Knowledge Management Capabilitiy, complementarities of knowledge Management Capabilitiy gives positive influence to corporate performance, Complementarities Information Technology Relatedness directly influence to company performance and information technology relatedness indirectly influence to corporate performance, being mediated by knowledge management capability